Carotid stenting: Is there an operator effect? A pooled analysis from the carotid stenting trialists' collaboration - Calvet, D; Mas, J; Algra, A; Becquemin, J; Bonati, L; Dobson, J; Fraedrich, G; Jansen, O; Mali, W; Ringleb, P; Chatellier, G; Brown, M (American Heart Association, 2013)
Background and Purpose Randomized clinical trials show higher 30-day risk of stroke or death after carotid artery stenting compared with surgery. We examined whether operator experience is associated with 30-day risk of stroke or death in the Carotid Stenting Trialists’ Collaboration database. Methods The Carotid Stenting Trialists’ Collaboration is a pooled individual patient database including all patients recruited in 3 randomized trials of stenting versus endarterectomy for symptomatic carotid stenosis (Endarterectomy Versus Angioplasty in patients with Symptomatic Severe Carotid Stenosis trial, Stent-Protected Angioplasty versus Carotid Endarterectomy trial, and International Carotid Stenting Study). Lifetime carotid artery stenting experience, lifetime experience in stenting procedures excluding the carotid, and annual number of procedures performed within the trial (in-trial volume), divided into tertiles, were used to measure operator experience. The outcome event was the occurrence of any stroke or death within 30 days of the procedure. The analysis was done per protocol. Results Among 1546 patients who underwent carotid artery stenting, 120 (7.8%) had a stroke or death within 30 days of the procedure. The 30-day risk of stroke or death did not differ according to operator lifetime carotid artery stenting experience (P=0.8) or operator lifetime stenting experience excluding the carotid (P=0.7). In contrast, the 30-day risk of stroke or death was significantly higher in patients treated by operators with low (mean ≤3.2 procedures/y; risk 10.1%; adjusted risk ratio=2.30 [1.36–3.87]) and intermediate annual in-trial volumes (3.2–5.6 procedures/y; 8.4%; adjusted risk ratio=1.93 [1.14–3.27]) compared with patients treated by high annual in-trial volume operators (>5.6 procedures/y; 5.1%). Conclusions Carotid stenting should only be performed by operators with annual procedure volume ≥6 cases per year.